Evaluation Study of Use of Interactive Multimedia 4.0-Based Teaching Materials - Mesterjon Mesterjon; Suwarni Suwarni; Dwi Rulismi; Sudarwan Danim (Budapest International Research and Critics University, 2023)
The evaluation carried out on the Utilization of Interactive Multimedia-Based Teaching Materials in student development courses is based on changes in